UNIVERSITY SUSTAINABILITY COMPETITIVE ADVANTAGE IN FACING TECHNOLOGICAL CHANGES - Setia, Bayu Indra; Yuniarsih, Tjutju; Sojanah, Janah; Kusnendi, Kusnendi; Ahman, Eeng; Pangestu, Erry (Faculty of Economics and Business, University of Pasundan, 2023)
The purpose of this study is to analyze sustainability's competitive advantage in the face of technological change mediated by knowledge management and organizational culture. The method used in this study is descriptive verification with model 6 analysis tools from Hayes's theory. The unit of analysis is six private universities that have accreditation A, with 204 respondents consisting of top management, middle management, and low management. The results obtained from the research show that technological change is affecting the university's sustainability competitive advantage, which is mediated by knowledge management and organizational culture. Technological change mediated by knowledge management has a major influence on and contribution to the university's sustainability competitive advantage as compared to organizational culture.